Leaf structure of the cerrado (Brazilian savanna) woody plants - Bieras, Angela Cristina [UNESP]; Sajo, Maria das Gracas [UNESP] (Springer, 2009)
With the aim of recognizing the commonest leaf pattern found in the woody flora of the cerrado (the Brazilian savanna) we analyzed the leaf anatomy of 30 representative species. The leaves are mostly dorsiventral and hypostomatic and covered by trichomes and a thick layer of wax and cuticle; the vascular bundles are surrounded by a sheath of fibers. The mesophyll has a developed palisade tissue, dispersed sclerified cells and idioblasts bearing crystals and phenolic compounds. We compared the results with those reported for other species (60 species) from the same biome and for the families that the studied species belong. The present study suggests that the xeromorphism observed for the cerrado leaves is related to the evolutionary history of this biome, since its first floristic elements must have faced deficient water conditions as well as the consequent soil acidity and toxicity. Therefore we may infer that the leaf anatomical pattern here observed was already present in the first elements of the cerrado and was selected to guarantee the survival of those species in the new environment. Furthermore, the xeromorphic features present in those leaves continue nowadays to help the plants protecting themselves from the different biotic and abiotic factors they are subjected to.
Keywords: Cerrado; Leaf anatomy; Leaf surface; Woody plants